HUBUNGAN PENGETAHUAN, SIKAP DAN SARANA PROTEKSI TERHADAP KESIAPSIAGAAN PENGHUNI DALAM MENGHADAPI KEBAKARAN DI RUSUNAWA UNDIP SEMARANG - Peni Nursalekha; Bina Kurniawan; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Preparedness activities take place before an emergency occurs with the aim of facilitating effective response and development of operational capacity when an emergency occurs. Rusunawa Undip as a place to live must assure its comfort, security and safety for the residents. A large number of residents live in the Rusunawa Undip resulting variety activities such as use of electric tools and cooking so that they have a high risk and fire risk increase. The purpose of this study was to analyze correlation between knowledge, attitudes and fire protection facility to fire preparedness in the Rusunawa Undip Semarang. This was a descriptive cross-sectional study using quantitative methods. The population of this research were 700 residents in Rusunawa Undip. The sample used of this research was 96 people with the taking technique of proportionate random sampling. Questionnaire and observation checklist were used as the instruments of this research. The observation sheet was used to check the suitability of existing fire protection facilities with the prevailing standards in Indonesia. Statistical analysis used was chi-square test. The result revealed that no variables related to fire preparedness, while the unrelated variables were knowledge (p-value 0.153), attitude (p-value 0.881), and fire protection facilities (p-value 0.691). The research recommends that manager to repairing and adding fire protection facilities, conducting socialization on fire preparedness, conducting periodic inspections of the fire protection facilities and making emergency procedures.